Cervical Spine Motion in Football Players During 3 Airway-Exposure Techniques - Ray, Richard (National Athletic Trainers Association, 2002)
Objective: Immediate rescue breathing, or cardiopulmonary resuscitation, may be necessary for the cervical spine-injured football player without removal of the helmet. The purpose of our study was to compare 2 pocket-mask insertion techniques with a face-mask rotation technique to determine which allowed the quickest initiation of rescue breathing with the least cervical spine motion. Design and Setting: In a biomechanics laboratory, 3 airway-preparation techniques were tested: chin-insertion technique (pocket mask inserted between the chin and face mask), eye-hole-insertion technique (pocket mask inserted through the face mask eye hole), and screwdriver technique (side loop straps removed using manual screwdriver followed by mask rotation). Subjects: One athletic trainer team and 12 National Collegiate Athletic Association Division III football players. Measurements: Time to initiate rescue breathing and induced helmet motion. Results: Both pocket-mask techniques allowed quicker initiation of rescue breathing. Cervical spine anterior-posterior displacement was greater for the chin technique than for the screwdriver or eye-hole techniques. Lateral translation was greater for the screwdriver technique than for either pocket-mask technique. Peak displacement from initial cervical spine position was greater for the chin technique than for the eye-hole technique. Conclusions: Both pocket-mask techniques allowed quicker initiation of rescue breathing than did rotation of the face mask via loop strap screw removal. The eye-hole insertion technique was faster and produced less cervical spine motion than the other 2 techniques. Each technique produced significantly smaller amounts of cervical spine displacement than that caused by cutting face-mask loop straps as reported earlier. We suggest a protocol for field management of cervical spine injuries in football players.